2022
DOI: 10.1111/ajco.13664
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos‐related lung cancer: Clinical characteristics and survival outcomes in an Australian cohort seeking workers compensation

Abstract: Background and objectives: Due to difficulties in identifying sufficient-sized cohorts there remains uncertainty about prognostic and clinical differences that may be unique to asbestos-related lung cancer (ARLC). In this study, we use the Helsinki Criteria to define a group of ex-workers with lung cancer attributable to asbestos exposure and investigate differences that may exist.Methods: A total of 529 patients seeking workers' compensation for their lung cancer were assigned to either ARLC or the non-ARLC b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is known that the combined effect of exposure to asbestos and tobacco smoke on lung cancer risk is more than additive and close to multiplicative; therefore, there is no scientific basis for contrasting these two factors in the risk assessment for individuals with both exposures (12, 48-51). We also observed that the majority of patients with lung cancer associated with asbestosis received a late diagnosis of cancer due to asbestosis-induced masking of symptoms (52). With reference to the occupations and respective production sectors of the 20 detected cases of lung cancer, our data agree with the recent meta-analysis on the impact of occupational exposure to asbestos on lung cancer in Italy (53).…”
Section: Discussionsupporting
confidence: 90%
“…It is known that the combined effect of exposure to asbestos and tobacco smoke on lung cancer risk is more than additive and close to multiplicative; therefore, there is no scientific basis for contrasting these two factors in the risk assessment for individuals with both exposures (12, 48-51). We also observed that the majority of patients with lung cancer associated with asbestosis received a late diagnosis of cancer due to asbestosis-induced masking of symptoms (52). With reference to the occupations and respective production sectors of the 20 detected cases of lung cancer, our data agree with the recent meta-analysis on the impact of occupational exposure to asbestos on lung cancer in Italy (53).…”
Section: Discussionsupporting
confidence: 90%
“…Radiation promoted the overexpression of oncogenes and the inactivation of tumor suppressor genes, thus leading to the occurrence and progression of lung cancer [58,59]. Lung cancer-related occupational exposure included asbestos, methyl chloride, chromium, nickel, and polycyclic aromatic hydrocarbons (PAHs) [60][61][62][63][64][65]. In a Chinese cohort involving 2,346 cases, Liu et al [64] found that exposure to occupational carcinogens was higher in areas with high/middle prevalence of lung cancer than in lowprevalence areas (58.02%-65.83% vs. 38.57%, respectively).…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Radiation promoted the overexpression of oncogenes and the inactivation of tumor suppressor genes, thus leading to the occurrence and progression of lung cancer [ 58 , 59 ]. Lung cancer‐related occupational exposure included asbestos, methyl chloride, chromium, nickel, and polycyclic aromatic hydrocarbons (PAHs) [ 60 , 61 , 62 , 63 , 64 , 65 ]. In a Chinese cohort involving 2,346 cases, Liu et al.…”
Section: Pathogenesismentioning
confidence: 99%